TP53 mutation in newly diagnosed acute myeloid leukemia and myelodysplastic syndrome - Pimjai Niparuck (2022)
Objectives: TP53 mutation is found frequently in therapy related acute myeloid leukemia (AML)/ myelodysplastic syndrome (MDS), AML and MDS patients with monosomy or complex karyotype. However, the prevalence and treatment outcome in TP53 mutated AML/MDS patients in Asian population are scarce. We therefore conducted this study to analyze the prevalence and the treatment outcomes of TP53 mutation in AML and MDS-EB patients. Methods: Patients with newly diagnosed AML and MDS-EB were recruited, extraction of deoxyribonucleic acid from bone marrow samples were done and then performing TP53 mutation analysis, using MassArray® System (Agena Bioscience, CA, USA). Results: A total of 132 AML/MDS patients were recruited, patients with de novo AML, secondary AML, MDS-EB1, MDS-EB2 and T-AML/MDS were seen in 66, 13, 9, 9 and 3%, respectively. TP53 mutation was found in 14 patients (10.6%), and prevalence of TP53 mutation in T-AML/MDS, secondary AML, de novo AML and MDS-EB patients were 50, 17.6, 9.2 and 8%, respectively. Three patients had double heterozygous TP53 mutation. Mutated TP53 was significantly detected in patients with monosomy and complex chromosome. Common TP53 mutation were R290C, T220C, A249S and V31I which V31I mutation was reported only in Taiwanese patients. Most variant allele frequency (VAF) of TP53 mutation in the study were greater than 40%. Three year-overall survival (OS) in the whole population was 22%, 3y-OS in AML and MDS-EB patients were 22 and 27%, respectively. The 1y-OS in patients with TP53-mutant AML/MDS were shorter than that in TP53 wild-type patients, 14% versus 50%, P = 0.001. In multivariate analysis, factors affecting OS in 132 AML/MDS patients was mutant TP53 (P = 0.023, HR = 1.20–7.02), whereas, WBC count> 100,000/μL (P = 0.004, HR = 1.32–4.16) and complex karyotype (P = 0.038, HR = 1.07–9.78) were associated with shorter OS in AML patients. Discussion: In this study, the prevalence of TP53 mutation in de novo AML and MDS-EB patients were low but it had impact on survival. Patients with monosomy or complex karyotype had more frequent TP53 mutation.